Analysis of pharmacotherapeutic approaches for multiple myeloma and correlated renal and pulmonary impairments: a retrospective real-world registry study in the Greater Gulf Region (REPAIR Study) - Alhejazi, Ayman; Alhuraiji, Ahmad; Nourallah, Abdulnaser; Alshehri, Abdulrahman; Usman, Binyam; ElGohary, Ghada; Malhan, Hafiz; Motabi, Ibraheem; Farsi, Khalil Al; Alshuaibi, Mohammed; Diab, Mohanad; Siddiqui, Mustaqeem; et al. (Frontiers in Oncology, 2025)
BackgroundMultiple myeloma (MM) is a plasma cell malignancy with significant unmet medical needs, particularly in the treatment of relapsed and refractory disease. This study aims to describe the disease characteristics, various treatment regimens, and outcomes among patients with Relapsed/Refractory Multiple Myeloma (RRMM) in the Greater Gulf region.MethodsA regional, retrospective study was conducted in Gulf countries to collect real-world data from the medical records of 148 patients with RRMM who relapsed 1–3 times in the past two years before the data collection period (July 2022 and February 2023).ResultsThe mean age of the study population was 59.4 years, and 64.2% of the participants were male. The VRd regimen (Bortezomib, Lenalidomide, and Dexamethasone) was the most frequent first-line therapy among transplant-ineligible patients (40.2%) and the most common induction and consolidation regimen (43.9% and 66.7%, respectively) in transplant-eligible patients. Meanwhile, Rd (Lenalidomide and Dexamethasone) was the most common maintenance regimen (75%). DKd (Daratumumab, Carfilzomib, and Dexamethasone), KPd (Carfilzomib, Pomalidomide, and Dexamethasone), and PVd (Pomalidomide, Bortezomib, and Dexamethasone) were the most widely used second, third, and fourth treatment lines, respectively (16.6%, 9.2%, and 12.5%). About 52.7% of patients were eligible for stem cell transplantation (SCT), and among them, a complete response (CR) was achieved in 47.7%. Furthermore, CR and very good partial remission rates decreased across all treatment lines. Renal impairment decreased across different treatment lines, from 23.6% in the first line to 6.3% in the fourth line. In contrast, respiratory complications demonstrated the highest incidence (>18%) in the 3rd and 4th treatment lines. Moreover, refractoriness to treatment increased from 1.3% in the first line to 34.6% in the fourth treatment line. Additionally, isatuximab was incorporated into 80%, 15%, and 5% of the regimens administered as second-, third-, and fourth-line treatments, respectively.ConclusionThis study provides valuable insights into the real-world management and treatment choices for RRMM, including the utilization of SCT and novel therapies such as isatuximab.